MINUTES ARE MUSCLE AND DELAY IS DEATH - Jibran, Muhammad Saad; Bahadar, Sher; Habib, Syed Abid; Gul, Adnan Mehmood (Journal of Postgraduate Medical Institute, 2020)
Objective: To determinutese the door to needle time (DNT) for thrombolysis of patients presenting with acute ST elevation myocardial infarction (STEMI) to emergency department, and its association with outcome of thrombolysis in terms of success and complications. Methodology: This cross-sectional study was conducted in chest pain clinic of Cardiology Unit, Lady Reading Hospital, Peshawar from February to May, 2017. Total 724 patients presenting with acute STEMI, fulfilling the inclusion criteria were included in the study by consecutive sampling. Demographic details, door to needle time (DNT), symptom to door time (SDT) and post-thrombolysis complications were recorded on a predesigned proforma. Mean ± S.D was calculated for continuous variables while frequencies and percentages were calculated for categorical data. Chi-square test was applied for association with a p value of <0.05 as significant. Regression model was used to determinutese odd ratios (OR) with a p value <0.05 as significant. Results: Mean age of the patients was 54.4 ± 8.4 years. Out of 724 patients, 50.8% were male with a mean SDT of 362.1 ± 92.1 and DNT of 34.42 ± 39.31 minutes. About 62.4% of patients were thrombolysed in less than 30 minutes, 27.1% in 30-60 minutes and 9.9% patients in >60 minutes. Percentage of successful thrombolysis decreased from 80.53% to 67.1% and 66.6% with increasing DNT from <30 minutes, 30-60minutes and >60 minutes with a p-value <0.01. Complication rate increased from 33.4% to 51.53% and 70.83% with an increase of 0.48 times to 2.25 times and 2.92 times in OR for failed thrombolysis while moving from <30 minutes to 30-60 minutes and >60 minutes respectively (p <0.01). Factors contributing to failure of thrombolysis included predisposing factors for coronary artery disease (CAD). Conclusion: Morbidity and mortality in patients of acute STEMI decreases if DNT is <30 minutes.